Application of Inverted Cathode Transverse Magnetic Field in Vacuum Arc During Surface Treatments Reusable Metals - C. Gustilo PhD, Reggie; Horiba, Yuya; Kanashiro Tang, Takehide; Takeda, Yuriko; Iwata, Soshi; Maeda, Yoshifumi; Iwao PhD, Toru (International Journal of Engineering and Technology, 2018)
The application of transverse magnetic field to control the vacuum arc cathode spot in surface treatment applications was conducted and analyzed its performance. An inverted cathode method of transverse magnetic field is proposed in this paper to serve as an alternative for the normal method of controlling the behavior of cathode spots during the treatment process. Experiment setup was designed to conduct and compare the behavior of the two methods. Several important parameters were considered such as the splitting frequency of the cathode spots, the number of droplets during the process, the linearity of the movement of the cathode spots and the surface roughness of the metal after the treatment process. It was shown that the proposed method (inverted method) gives better linearity in terms of movement and suffers from increased roughness.